2021
DOI: 10.2196/27686
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Scope of Digital Public Health and Its Implications for Policy, Practice, and Research: Protocol for a Scoping Review

Abstract: Background There has been rapid development and application of digital technologies in public health domains, which are considered to have the potential to transform public health. However, this growing interest in digital technologies in public health has not been accompanied by a clarity of scope to guide policy, practice, and research in this rapidly emergent field. Objective This scoping review seeks to determine the scope of digital health as descr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Our methods and findings about the definition of the field have been described in detail elsewhere. 5 , 10 Here we focus on the challenges and recommended solutions to support the development and implementation of digital public health interventions. We followed Arksey and O’Malley's framework for scoping reviews, 11 with adaptations suggested by Levac et al.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our methods and findings about the definition of the field have been described in detail elsewhere. 5 , 10 Here we focus on the challenges and recommended solutions to support the development and implementation of digital public health interventions. We followed Arksey and O’Malley's framework for scoping reviews, 11 with adaptations suggested by Levac et al.…”
Section: Methodsmentioning
confidence: 99%
“…We excluded primary research studies like trials and cross-sectional studies, given that our focus was on assessing the discourse around digital technologies in public health and not specifically on assessing any digital interventions in public health. 10 We included articles published in English between January 2000 and June 2020. Included titles and abstracts were exported to Covidence® for further review and citation management.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings presented in this study are part of a larger scoping review aimed at conceptualizing the breadth of digital public health, the methods for which are described elsewhere [ 15 ]. For this study, we used the framework by Arksey and O’Malley [ 16 ] with adaptations as suggested by Levac et al [ 17 ].…”
Section: Methodsmentioning
confidence: 99%